Airway epithelial cells mount an early response to mycobacterial infection - Barclay, Amy M.; Ninaber, Dennis K.; van Veen, Suzanne; Hiemstra, Pieter S.; Ottenhoff, Tom H. M.; van der Does, Anne M.; Joosten, Simone A. (Frontiers in Cellular and Infection Microbiology, 2023)
Lung epithelial cells represent the first line of host defence against foreign inhaled components, including respiratory pathogens. Their responses to these exposures may direct subsequent immune activation to these pathogens. The epithelial response to mycobacterial infections is not well characterized and may provide clues to why some mycobacterial infections are cleared, while others are persistent and pathogenic. We have utilized an air-liquid interface model of human primary bronchial epithelial cells (ALI-PBEC) to investigate the epithelial response to infection with a variety of mycobacteria: Mycobacterium tuberculosis (Mtb), M. bovis (BCG), M. avium, and M. smegmatis. Airway epithelial cells were found to be infected by all four species, albeit at low frequencies. The proportion of infected epithelial cells was lowest for Mtb and highest for M. avium. Differential gene expression analysis revealed a common epithelial host response to mycobacteria, including upregulation of BIRC3, S100A8 and DEFB4, and downregulation of BPIFB1 at 48 h post infection. Apical secretions contained predominantly pro-inflammatory cytokines, while basal secretions contained tissue growth factors and chemokines. Finally, we show that neutrophils were attracted to both apical and basal secretions of infected ALI-PBEC. Neutrophils were attracted in high numbers to apical secretions from PBEC infected with all mycobacteria, with the exception of secretions from M. avium-infected ALI-PBEC. Taken together, our results show that airway epithelial cells are differentially infected by mycobacteria, and react rapidly by upregulation of antimicrobials, and increased secretion of inflammatory cytokines and chemokines which directly attract neutrophils. Thus, the airway epithelium may be an important immunological component in controlling and regulating mycobacterial infections.